Range of motion limitations of the upper body in obese female workers - Cau, Nicola; Cimolin, Veronica; Brugliera, Luisa; Ventura, Giuseppe; Galli, Manuela; Capodaglio, Paolo (La Medicina del Lavoro, 2017)
Background: The prevalence of obesity is increasing worldwide, and the economic consequences of an increased percentage of obese workers are relevant in terms of health costs and absences from work. Obesity is associated with reduced participation in the workforce, increased absence from work, disability and health costs, lower salaries and reduced productivity. Objectives: We aimed at quantifying the limitations in range of motion (ROM) of the upper limb and the trunk of obese workers during basic occupational tasks. Methods: One group of 15 obese female subjects (BMI: 42.10±9.10 kg/m2) and one control group of 13 normal-weight female subjects were recruited. Three group of tasks were selected as representative of basic occupational movements: 1) upper limb movements (reaching, abduction-adduction, frontal elevation); 2) trunk movements (lateral bending, rotation); 3) whole body movement (target task). Results: We observed significant range of motion limitations in lateral and frontal upper arm elevation. Statistically significant difference in terms of center of pressure (the point of application of the ground reaction force measured by means of force platform) excursions was observed for lateral bending and trunk rotation tasks. Conclusions: Our results show that obese subjects have significant range of motion limitations of the upper body during basic occupational activities. This study provides quantitative evidence of these limitations of obese workers and may serve occupational specialists to allocate them to adequate jobs and reduce the rate of work-related musculoskeletal disorders.